Approaching minimal cognition: introduction to the special issue. (December 2020) - Brancazio, Nick; Segundo-Ortin, Miguel; McGivern, Patrick
This special issue highlights the growing interdisciplinary interest in minimal cognition, bringing together a number of philosophers and scientists interested in investigating where, how, and why cognition arises. In what follows, we introduce the topic of minimal cognition by giving a brief look at debates and discussions about the lower bounds of cognition, minimally cognitive behaviors, and the possibility of life-mind continuity. Afterwards, we offer a short summary of each of the contributions to this issue. In the spirit of the Minimal Cognition conferences at the University of Wollongong at which the contributors participated, we hope this special issue will enrich the current state of minimal cognition research by putting a number of different disciplines and approaches into conversation.